Post-editing quality: Analysing the correctness and necessity of post-editor corrections - Koponen, Maarit; Salmi, Leena (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2018)
Post-editing (PE) machine translations (MT) has become an increasingly common practice in the translation field in recent years. Research has investigated, among other issues, the types of error corrected by post-editors, but less emphasis has been placed on the corrections themselves and how they reflect MT errors. This article presents a pilot study analysing the edits made by five student post-editors in an English–Finnish post-editing task. We analyse the correctness and necessity of the edits. Our results show that, whereas most edits performed in the task are correct, a significant number of them (34%) are unnecessary. The findings suggest that specific types of edit, such as word-order changes and deletions of personal pronouns, are generally unnecessary for this language pair, which may have implications for post-editing practice and training.